2022
DOI: 10.1186/s12989-021-00439-6
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to silicates and systemic autoimmune-related outcomes in rodents: a systematic review

Abstract: Background Autoimmunity can result from the interplay between genetic background and effects of environmental and/or occupational exposure to hazardous materials. Several compounds, including silica dust, have been linked with systemic autoimmunity and systemic autoimmune diseases, based on epidemiological evidence. For asbestos, a strong link with systemic autoimmune diseases does not yet exist, however, several studies have documented features of autoimmunity following asbestos exposure. Even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 96 publications
0
6
0
Order By: Relevance
“…In addition, when we took an occupational history, the association of regular silica exposure helped us to think laterally. The literature reported that auto-immune diseases were also linked to silica exposure [ 11 , 12 ], and in our case, the patient has had silica exposure for several years as a sculptor. It led us to consider the previously reported associations between silica dust exposure and autoimmune disease.…”
Section: Discussionmentioning
confidence: 73%
“…In addition, when we took an occupational history, the association of regular silica exposure helped us to think laterally. The literature reported that auto-immune diseases were also linked to silica exposure [ 11 , 12 ], and in our case, the patient has had silica exposure for several years as a sculptor. It led us to consider the previously reported associations between silica dust exposure and autoimmune disease.…”
Section: Discussionmentioning
confidence: 73%
“…NOD/ShiLtJ mice and C57BL/6J mice are known to exhibit significantly distinct baseline immunophenotypic characteristics. C57BL/6J mice were included as a well-studied strain for silicosis and lung inflammation, not spontaneously developing autoimmunity nor developing autoimmune disease upon silica exposure ( 41 ). NOD/ShiLtJ mice, on the other hand, have a chronic inflammatory state, represented by high serum immunoglobulin levels compared to C57BL/6J mice ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…In animal experiments, the relationship between silica exposure, autoimmune diseases, and serum autoantibody positivity has been shown in many studies. 23 Proteinuria, renal immunoglobulin G, and C3 deposits were detected after exposure of lupus-prone NZM2410 mice with crystalline silica; positive markers, such as antinuclear antibody (ANA) and anti-DNA, were observed after subcutaneous administration of sodium silicate to a group of rats; 8 and silicosis exposure in mice infected with lymphocytic choriomeningitis virus has been shown to induce severe GN with elevated autoantibody levels. It has, therefore, been suggested that autoimmunity may be activated by silicosis exposure in the case of chronic viral infection as part of the pathogenesis of a prototype autoimmune disease like SLE.…”
Section: Discussionmentioning
confidence: 99%